Generation of M2c Macrophages Using IL-10 Exposure In Vitro - Alif, Iffan; Kurniawan, Dicky Zulfa F; Wilaksono, Bhirau; Susanto, Indra (Stem Cell and Cancer Research (SCCR), 2024)
Background : Macrophages are essential cells of the innate immune system that highly adaptable and play vital roles in tissue homeostasis, immune regulation, and development. Among their various phenotypes, the M2c subtype—induced by IL-10 and TGF-β—is known for its regulatory functions, high phagocytic capacity, and pro-angiogenic potential. This study aimed to investigate whether M2c polarization via IL-10 stimulation occurs in a dose-dependent manner by differentiating human monocyte-derived macrophages using IL-10 at concentrations of 5, 10, and 20 ng/mL. Methods : IL-10 expression levels were assessed by ELISA and qPCR. The results demonstrated a clear dose-dependent increase in IL-10 expression across both methods. Results : ELISA measurements showed IL-10 levels increasing from a mean of 3.2±0.7 pg/mL in untreated controls to 19.34±2.3 pg/mL (5 ng/mL), 35.5±7 pg/mL (10 ng/mL), and 67.2±5.8 pg/mL (20 ng/mL). Similarly, qPCR analysis revealed a corresponding increase in IL-10 gene expression, with relative fold changes from 1±0 (untreated control) to 3.1±0.4, 6±1.3, and 10.1±1.6, respectively. Conclusions : These findings indicate that IL-10 induces M2c macrophage polarization in a dose-dependent manner, providing insight into optimized conditions for generating regulatory macrophage populations for potential therapeutic applications.